Is it possible to measure social entrepreneurship in firms? - Marta Peris Ortiz; Carlos Rueda Armengot; Daniel Palacios Marqués (Management Letters/Cuadernos de Gestión, 2016)
This study defines and proposes a measurement scale for social entrepreneurship (SE) in its broadest sense. The broad definition of SE covers for-profit firms that use social aims as a core component of their strategy. By pursuing social aims, these firms can boost the value of their products or services for consumers or exploit new business areas. Under this broad definition of SE, profit-seeking and the pursuit of social aims converge, thereby revealing a form of SE that has received little attention in either theoretical or empirical research. To fill this research gap, the present study proposes a measurement scale to measure broad SE in firms. The process used to build the scale draws upon research by Churchill (1979) and DeVellis (1991) and combines the Delphi technique, a pre-test questionnaire and structural equation modelling. The main aim of this research is to develop a scale capable of measuring broad SE in firms. The theoretical basis for the scale is supported by an empirical study in the hotel sector. The scale provides a valid, reliable instrument for measuring broad SE in firms. The scale meets all sociometric properties required of measurement scales in the social sciences, namely dimensionality, reliability and validity.